'A particular spirit of enterprise': Bristol and Liverpool slave trade merchants as entrepreneurs in the eighteenth century - McDade, Katie (2011)
It is well known that Liverpool surpassed Bristol as Britain's premier slave trading port in the mid-eighteenth century, but the reasons for Liverpool's dominance remain debated. In this comparative research, the theoretical framework of entrepreneurship and various notions of capital, including financial, human and social, accessed through merchants' associational networks is employed to determine whether or not Liverpool merchants were more entrepreneurial in the trade which in turn made them more successful. An interdisciplinary methodology that embraces concepts from both economic and business history as well as social network and socio-cultural analysis is used to ascertain how slave merchant networks in both ports operated and managed their trade.